PS-4 Evaluating the Effects of Artificial Rainfall and Permethrin Resistance Status on the Efficacy of Common Pour-On Formulation Delivered to Beef Heifers in a Controlled Environment. (22nd October 2022) - Castro, Dalila; Sanchez-Sandoval, Ulises A; Ramirez, Jovannah; Smythe, Brandon G
Abstract: The objective of this study is to determine the impact of rainfall on the duration of efficacy of a commercial pour-on against susceptible (SS) and permethrin resistant (PR) horn flies. Eighteen Angus-Hereford crossbred heifers (BW) were used in a completely randomized design with repeated measures to determine the efficacy and longevity of a permethrin-based pour-on. Animals were randomly assigned to one of two fly infestations (SS or PR) and within infestation to one of three rainfall regimens [no rain (NR), no rain with a pour-on (NP) treatment, and rain with a pour-on (RP) treatment]. All heifers were housed in outdoor roofed pens within the corresponding treatment group and animals with NP and RP groups were treated once on day 0 at the label rate. Once a week for four weeks all animals were placed into individual indoor screened rooms where the fly infestations were administered. Live fly counts were acquired 24 h following each infestation. Animal with RP received approximately 2.54 cm of artificially provided rainfall within 2 hours following each weakly horn fly count. A treatment × day x fly interaction (P < 0.01) was observed. In general, NR groups maintained higher (P < 0.05) populations of SS and PR for 22 and 8 days post-treatment, respectively. Regardless, of fly species, rainfall had no (P > 0.05) influence on product efficacy. In conclusion, insecticide resistance status appears to be more influential than heavy rainfall in the longevity of permethrin-based pour-on products.